As medidas de flexibilização da execução da pena de prisão - Boavida, Joaquim António Lourenço (2016)
This study concerns the flexibilization measures of imprisonment, as a mean to mitigate the rigidity of its execution, taking into account all the cases in which it is allowed for a sentenced individual to temporarily leave the prisional establishment or to remain in a state of more freedom and less control. It analyzes the prison sentence’s evolution through time in Portugal so as to understand the appearance and development of softening measures of imprisonment. The study follows such measure’s progression, since its first appearance until now, and thoroughly develops its current legal regime. Moreover, it compares the measure’s regime to other seven foreign countries, four of which are European and three from Latin American. The study’s main scope is the relationship between the end of prison sentences and its softening, especially when it comes to the aspect of the projection of those purposes in the legal regime and the actual implementation of the mentioned measures. In order to do so, it analyzes the results when granting such forms of attenuation and identifies its virtues and shortcomings, as well as the main problems of the penitentiary system that hinder an adequate social reintegration of former criminals in society. It is concluded that the practical results of the flexibilization measures focus on avoiding desocialisation but have a minor effect in preventing a relapse (criminal recidivism).